LITERASI DIGITAL DI ERA ADAPTASI KEBIASAAN BARU - Oom Nurrohmah (Nusantara Journal of Information and Library Studies (N-JILS), 2021)
This study aims to determine the importance of digital literacy in the New Habit Adaptation Era that must be implemented by libraries through various existing services. The research method used is a literature study. The results of the study show that the period of Adaptation to New Habits caused by the Covid-19 pandemic since the beginning of 2020 has brought changes to all activities carried out by humans. Including the library which is a public service institution and media literacy. In providing information services and media literacy, having a library has a strategic role to educate the public, not only as a source of information and knowledge for every user. However, the library also acts as a lifelong learning medium that supports improving the quality of public education. This makes the library must be adaptive to the times in accordance with the dynamic and changing needs of users. One of the changes in user needs is influenced by the development of Information and Communication Technology which coincides with the pandemic period. Libraries must transform their management and service activities that lead to the use of technology which has become a necessity. This library transformation aims so that existing resources can be utilized by users optimally, so digital literacy needs to be developed to build the nation's character. Dimensions of digital literacy include tools and systems; information and data; sharing and creation; and historical and cultural contexts. Thus, the digital literacy capabilities possessed by library human resources and users will build a strong synergy in the use of libraries.Keywords: digital literacy; new normal; library ABSTRAKPenelitian ini bertujuan untuk mengetahui pentingnya literasi digital di Era Adaptasi Kebiasaan Baru yang harus diterapkan oleh perpustakaan melalui berbagai layanan yang ada. Metode penelitian yang digunakan adalah studi literatur. Hasil penelitian menunjukkan bahwa masa Adaptasi Kebiasaan Baru yang diakibatkan oleh pandemi Covid-19 sejak awal Tahun 2020 telah membawa perubahan pada seluruh aktivitas yang dilakukan manusia. Termasuk di perpustakaan yang merupakan institusi pelayanan publik dan media literasi. Dalam memberikan layanan informasi dan media literasi memiliki perpustakaan memiliki peran strategis untuk mencerdaskan masyarakat tidak hanya sebagai sumber informasi dan pengetahuan bagi setiap pemustaka. Namun, perpustakaan juga berperan sebagai media pembelajaran sepanjang hayat yang mendukung peningkatan kualitas pendidikan masyarakat. Hal ini menjadikan perpustakaan harus adaptif terhadap perkembangan zaman sesuai dengan kebutuhan pemustaka yang dinamis dan berubah-rubah. Perubahan kebutuhan pemustaka ini salah satunya dipengaruhi oleh perkembangan Teknologi Informasi dan Komunikasi yang bertepatan dengan masa pandemik. Perpustakaan harus melakukan transformasi pengelolaan maupun kegiatan layanannya yang mengarah kepada penggunaan teknologi yang telah menjadi suatu keniscayaan. Transformasi perpustakaan ini bertujuan agar sumber daya yang ada dapat dimanfaatkan oleh pemustaka secara optimal, maka literasi digital perlu dikembangkan untuk membangun karakter bangsa. Dimensi literasi digital meliputi alat dan sistem; informasi dan data; berbagi dan kreasi; serta konteks sejarah dan budaya. Dengan demikian, kemampuan literasi digital yang dimiliki oleh sumber daya manusia perpustakaan dan pemustaka akan terbangun sinergi yang kuat dalam pemanfaatan perpustakaan.